Aktivitas Anti-Inflamasi In Vitro Ekstrak Etanol Daun Vernonia amygdalina DELILE Dengan Pengujian Stabilisasi Membran - Muhammad Khairul Nuryanto; Swandari Paramita; Abdillah Iskandar; Sjarif Ismail; Andre Kusuma Ruslim (Jurnal Sains dan Kesehatan, 2017)
Inflammation is a normal process in the human body as a response to injury from the healing process. Meanwhile, chronic inflammation will cause new health problems to patients. Anti-inflammatory agents generally used for those conditions, have several side effects to patients. The objective of this research was to find alternative anti-inflammatory agents, especially from natural sources. Vernonia amygdalina Delile knew locally as “Daun Bismillah” belong to family Apiaceae is one of those potential natural sources for alternative anti-inflammatory agents. This plant is known as traditional medicine and used as material in this research. The experimental method of in vitro anti-inflammatory measurement using membrane stabilization activity for ethanol extracts of V. amygdalina leaves. The results showed that significant differences of EC50 (p<0.05) were achieved between indomethacin as the positive control with V. amygdalina leaves extracts for concentration 1% and 10%. EC50 of leaves ethanol extract of V. amygdalina showed the potential anti-inflammatory activities. It could be concluded that V. amygdalina leaves ethanol extracts to have anti-inflammatory activities, which could be further developed as a new natural source of the anti-inflammatory agents.